Denosumab-Induced Proximal Myopathy in a Child - PV, Sripadma; Jain, Rajendra S.; Agarwal, Jitesh (Journal of Pediatric Neurology, 2021)
Denosumab, a fully humanized monoclonal antibody, has been used for the treatment of osteoporosis, in complications resulting from bone metastatic disease and in giant cell tumor in both adults and skeletally mature adolescents. Denosumab is an inhibitor of the receptor activator of nuclear factor kappa-B ligand and belongs to a new class of antiresorptive medications. We report a unique case of myopathy in a 13-year-old boy prescribed denosumab for enchondromatosis. The boy presented with hypovitaminosis D, elevated parathyroid hormone, suppressed alkaline phosphatase, hypocalcemia, and hypophosphatemia after a single dose of denosumab. Our case points to altered calcium–vitamin D homeostasis induced by denosumab. Myopathy associated with denosumab has not been described previously in children. Early recognition of myopathy and adequate supplementation with calcium–vitamin D may ensure a more favorable clinical outcome.
Keywords: denosumab; myopathy; hypovitaminosis D; calcium; weakness